The three INGs: Recruiting, training and retaining - Lilley, Spencer C (Massey University, 2000)
The purpose of this paper is to address the problem of firstly how we recruit Maori to our profession, train them in the range of skills required to be successful and lastly how to stop them leaving the profession. The preparation of this paper has been assisted through an informal email survey of Te Ropu Whakahau members. Comments from the survey are used throughout the presentation to illustrate a number of key issues that emerged from the survey results. Later in the presentation I will also provide examples of overseas initiatives to recruit ethnically diverse peoples to the Library profession.
Paper presented at the Library and Information Association of New Zealand Aotearoa 2000 Conference 15 –18 October 2000, Christchurch.
Keywords: Librarianship; Maori; Fields of Research::220000 Social Sciences, Humanities and Arts-General